Effectiveness of Total Contact Cast in Patients with Diabetic Neuropathic foot Ulcers - Muqadas Mazhar, Muqadas Mazhar; Ajla Javed, Ajla Javed; Obaid -Ur-Rehman, Obaid -Ur-Rehman; Saif Ullah, Saif Ullah (Resident Journal of Rawalpindi Medical University, 2024)
Introduction: To assess the effectiveness of Total Contact Cast (TCC) in treating diabetic neuropathic foot ulcers, including percentage reduction in ulcer surface area and healing time. Methods: A quasi-experimental investigation took place in Benazir Bhutto Hospital Rawalpindi, Medical University, for six months, from August 1st, 2023 to January 31st, 2024. The study included thirty diabetes patients with non-ischemic neuropathic foot ulcers up to grade 2A, as classified by the University of Texas. The pre-intervention ulcer size was measured with metal ruler. Debridement was performed in some individuals to remove necrotic tissue, calluses, and foreign objects and Total Contact Cast (TCC) was applied. TCC was repeated every two weeks until the ulcer was healed. Post-intervention ulcer size measurements were taken. The key outcome measures were percentage reduction in ulcer surface area and time to heal in the cast. Results: Twenty-two patients (73.3%) were males, whereas eight (26.7%) were female. The patients’ average age was 59±7 years. Every patient had NIDDM. The majority of forefoot and mid-foot ulcers in the current study healed with a total contact cast. Average healing time was 39 days (three cast’s duration). Patients identified as grade 1A recovered completely over the research period, but those classified as grade 2A showed a considerable reduction in ulcer size until the eighth week. Among Thirty patients with diabetic Non-ischemic neuropathic foot ulcers, the mean ulcer size (cm²) at baseline was 4.6583±2.41090 SD. It changed to 1.3550±1.26228 SD at the end of the trial. The ulcer size at baseline and the ulcer size at the 8-week followup were compared using a paired sample t-test. The percentage reduction in ulcer size surface area from baseline at the eighth week was 71% with total contact cast. P< 0.05 was considered significant. Conclusion: The results of the study showed that total contact cast was a successful therapy for neuropathic diabetic foot ulcers of Texas grade up to 2A that were located in the forefoot and midsole region. Keywords: Diabetic Neuropathic foot ulcers, Total contact cast, offloading.